Formulation and in vitro evaluation of mouth dissolving tablets of levosulpiride - Irfan Sohail; Noman Ahmad; Muhammad Majid; Waqas Ahmad Nasir; Shan Malik; Tuseef Tahir (AMMANIF, 2019)
Objective: The objective of this study was to formulate and optimize a mouth dissolving formulation of levosulpiride. Method: Levosulpiride mouth dissolving tablet having D2-dopamine receptor antagonistic activity were made by direct compression using microcrystalline cellulose, mannitol, povidone and a disintegrant sodium starch glycolate. Thus, formulating levosulpiride into amouth dissolving dosage form would provide fast relief. Results: The tablets were evaluated for weight variation, drug content, content uniformity, hardness, friability, in-vitro disintegration time and in-vitro drug release. The results show that the presence of a superdisintegrant and mannitol is desirable for orodispersion. Conclusion: Formulations satisfied the limits of orodispersion with a dispersion time of less than 60 sec, optimized drug released within 30 min and the formulations followed first order linear kinetics. So, it is feasible to formulate mouth dissolving tablets of levosulpiride with acceptable disintegration time, rapid drug release and good hardness as an alternative to conventional tablet.